Effects of Cu and Mg alloying and low-temperature aging on microstructure characteristics and mechanical properties of heat treatment-free cast Al–Si–Cu–Mg alloys - Xinxin Ma; Yanpeng Pan; Liwen Chen; Hua Hou; Jibo Hou; Yuhong Zhao (Journal of Materials Research and Technology)
The effects of low-temperature aging and the Cu/Mg ratio at varying Cu and Mg concentrations on the microstructure and tensile characteristics of Al–Si–Cu–Mg alloys processed through different casting techniques were examined using Pandat thermodynamic calculation software. The results indicate that the as-cast Al–Si–Cu–Mg alloys exhibit multiple intermetallic phases, with their formation kinetics strongly dependent on both Cu/Mg ratios and elemental concentrations. Meanwhile, microstructural observations of T5-age alloys showed that different casting processes affect the morphology and distribution of the nano-precipitates, consequently governing the strength and plasticity of the alloys.Specifically, the Al–10Si–1Cu-0.6 Mg alloy (Cu/Mg = 1.7) demonstrated an optimal combination of strength and ductility, attributed to the refined size and content of its precipitates.